The emergence of arboviruses changes the profile of viral meningitis in Salvador, Bahia: A case series - Dias, Tamiris T.; Tauro, Laura B.; Macêdo, Lara E. N.; Brito, Liz O.; Ribeiro, Victor H. O.; Santos, Cleiton S.; Jacob-Nascimento, Leile C.; Vilas-Boas, Letícia S.; Amado, Caio; Barbosa, Paula S.; Reis, Joice N.; Campos, Gubio Soares; et al. (Frontiers in Tropical Diseases, 2022)
Background Recently, different arboviruses became endemic in Brazil mostly causing acute febrile illnesses, however, neurological manifestations have also been reported. This study aimed to investigate which viruses were involved in the meningitis etiology and the contribution of the circulating arboviruses in Salvador, Bahia, Brazil. Methods From June 2014 to February 2016, 170 patients with suspected viral meningitis were identified in Couto Maia Hospital, Salvador-BA, Brazil. Their CSF samples were investigated for possible viral etiology by reverse transcription-PCR (RT-PCR) for different arboviruses: DENV, ZIKV and CHIKV; and for the EV; and by PCR for the HHV1-5 complex (HSV1-2, VZV, EBV and CMV). Also, ELISA was carried out in a subgroup of remaining samples for detection of DENV IgM and NS1 antigen, CHIKV IgM and ZIKV IgM. Results Thirty-seven patients were PCR or ELISA positive for at least one of the studied viruses (overall positivity 21.8%). EV was the agent most frequently detected (10 cases; 27.0%), along with all four DENV serotypes (10 cases; 27.0%); followed by CHIKV (6 cases; 16.2%), ZIKV (6 cases; 16.2%), and Varicella zoster virus (VZV) (1 case; 2.7%). Four cases (10.8%) presented viral co-infection detected: DENV1 + CHIKV, DENV1 + EV, DENV4 + ZIKV, and CHIKV + ZIKV. Arboviruses (DENV, CHIKV and ZIKV) accounted for the great majority of cases (26 cases; 70.3%) of all single and co-infections: DENV has been the most frequently detected arbovirus (13 cases; 35.1%). Among non-arboviral meningitis, the most common etiology was the EV (11 cases; 29.7%). Conclusions Arboviruses accounted for the majority of identified viruses among patients with suspected viral meningitis. In areas where they are endemic it is crucial to increase viral surveillance and consider them in the differential diagnosis of meningitis.